The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1987
DOI: 10.1159/000118335
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Insulin, Tryptophan and Serotonin Levels during the Glucose Tolerance Test among Habitually Violent and Impulsive Offenders

Abstract: Insulin activity in plasma and the concentrations of tryptophan and serotonin were measured during the glucose tolerance test (GTT) in habitually violent and impulsive male offenders and in psychiatric personnel as controls. Insulin was enhanced in the intermittent explosive disorder; at the same time the concentration of plasma tryptophan and the ratio of tryptophan to large neutral amino acids were on a high level and tryptophan even increased in many cases during GTT. Serotonin values did not differ. Many o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0
4

Year Published

1991
1991
2010
2010

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 15 publications
3
31
0
4
Order By: Relevance
“…Post hoc analyses produced an interesting preliminary result showing that when the women were divided into two groups-high and low fasting control plasma Trp-there was a distinct difference in aggressive responsivity to CNS 5-HT manipulation. Similar results with men have established a relationship between higher baseline plasma Trp and elevated aggressive behavior (Eriksson and Lidberg 1997;Møller et al 1996;Virkkunen and Närvänen 1987;Wingrove et al 1999). The results of this study show that it was the high fasting control plasma Trp women who increased aggressive responding under depletion conditions; however, unlike the men, these women also showed significant decreases in aggression when plasma Trp was augmented.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Post hoc analyses produced an interesting preliminary result showing that when the women were divided into two groups-high and low fasting control plasma Trp-there was a distinct difference in aggressive responsivity to CNS 5-HT manipulation. Similar results with men have established a relationship between higher baseline plasma Trp and elevated aggressive behavior (Eriksson and Lidberg 1997;Møller et al 1996;Virkkunen and Närvänen 1987;Wingrove et al 1999). The results of this study show that it was the high fasting control plasma Trp women who increased aggressive responding under depletion conditions; however, unlike the men, these women also showed significant decreases in aggression when plasma Trp was augmented.…”
Section: Discussionsupporting
confidence: 84%
“…Serotonin dysfunction has been correlated with impulsive and violent criminal behaviors (Brown et al , 1982Lidberg et al 1985;Limson et al, 1991;Virkkunen and Närvänen 1987;Virkkunen et al 1994aVirkkunen et al , 1994b, alcohol abuse and dependence (Badawy et al 1995;Ballenger et al 1979;Banki 1981;Borg et al 1985;Moss 1987;Roy and Linnoila 1989), Gilles de la Tourette's syndrome (Butler et al 1979;Cohen et al 1978Cohen et al , 1979, bulimia (Jimerson et al 1990(Jimerson et al , 1992, and suicide attempts (Asberg et al 1976(Asberg et al , 1986Banki and Arato 1983;López-Ibor et al 1985), as well as with children institutionalized for aggressive behavior (Kruesi 1989;Kruesi et al 1990Kruesi et al , 1992.…”
Section: Plasma L -Tryptophan (Trp) Reductions Have Been Related To Amentioning
confidence: 99%
See 1 more Smart Citation
“…Serotonin-mediated behavioral deficits are thought to result in part from an inability to maintain a homeostatic response in a number of physiological systems (Virkkunen et al 1989a;Virkkunen and Narvanen 1987;Virkkunen et al 1994). Various lines of evidence indicate that central serotonin neurotransmission contributes to regulation of sleep-wake cycles and circadian activity patterns.…”
Section: Men With Low Cns Serotonin Turnover As Measured By Cerebrosmentioning
confidence: 99%
“…Research using nonhuman primates has replicated and extended many of these findings (Higley et al 1996a;Higley et al 1992a;Higley et al 1996b;Kaplan et al 1994;Mehlman et al 1995;Mehlman et al 1994;Mehlman et al 1997;Raleigh 1987;Raleigh et al 1983a;Raleigh et al 1983b;Raleigh et al 1980;Raleigh and McGuire 1994). Further, this research has demonstrated that inter-individual differences in CSF 5-HIAA concentrations are stable across time and experimental settings and can be attributed to genetic and early environmental influences that produce lasting modifications in the CNS serotonin response (Higley et al 1996b;Higley et al 1994;Higley et al 1996a).Serotonin-mediated behavioral deficits are thought to result in part from an inability to maintain a homeostatic response in a number of physiological systems (Virkkunen et al 1989a;Virkkunen and Narvanen 1987;Virkkunen et al 1994). Various lines of evidence indicate that central serotonin neurotransmission contributes to regulation of sleep-wake cycles and circadian activity patterns.…”
mentioning
confidence: 92%